Augmenting Public Service Delivery Through Online Feedback Systems. (September 2020) - Sapru, Yudhishthira
The importance of citizen feedback on public services can never be undermined. However, for many public service organisations, citizens' feedback is the least of the priorities. Technology has not only helped in improving public service delivery but also the feedback part of it. This article highlights the importance of feedback in the context of public service delivery. It also identifies the challenges faced in implementing feedback systems, besides highlighting critical success factors. Further, it has been discussed how online feedback systems have transformed the way citizens interact with public authorities. This article also discusses the Rapid Assessment System (RAS), which is a generic technology-enabled platform for seeking real-time citizen feedback on public services.